Optimasi Konten Digital untuk UMKM Naik Kelas Bekasi : Menarik Pelanggan di Era Digital - Basudani, Wahid Akbar; Givan, Bryan; Purwanto, Oby Eko (Indonesian Journal of Society Engagement, 2024)
This Community Service activity aims to provide training for entrepreneurs who are members of the Bekasi Upgrade SME Community where these SME entrepreneurs need knowledge and resources in carrying out digital marketing strategies in the context of business development. The method used is by giving lectures or presenting material directly. consisting of an explanation of what digital marketing is, creating marketing content and using social media marketing. By knowing the concept of digital marketing and using digital, SME content entrepreneurs can increase the sales potential of their products and attract customers from various regions so that they can expand their market and the business they build can grow in a relatively fast time.